Advances in motivation science. - Elliot, Andrew J. (Elsevier/Academic Press, 2016)
Advances in Motivation Science, Volume Four, is the latest in Elsevier's brand new serial on the topic of motivation science. It is a timely serial on an area of study that has not only been a mainstay of the science of psychology, but also a major influence in early dynamic and Gestalt models of the mind and fundamental to behaviorist theories of learning and action. The advent of the cognitive revolution in the 1960 and 70s eclipsed the emphasis on motivation to a large extent, but in the past two decades motivation has returned en force. Today, motivational analyses of affect, cognition, and behavior are ubiquitous across psychological literatures and disciplines. In essence, motivation is not just a "hot topiciA on the contemporary scene, but is firmly entrenched as a foundational issue in scientific psychology. This volume brings together internationally recognized experts who focus on cutting-edge theoretical and empirical contributions in this important area of psychology.